Glyco-engineered HEK 293-F cell lines for the production of therapeutic glycoproteins with human N-glycosylation and improved pharmacokinetics. (5th January 2021) - Uhler, Rico; Popa-Wagner, Ruth; Kröning, Mario; Brehm, Anja; Rennert, Paul; Seifried, Annegrit; Peschke, Madeleine; Krieger, Markus; Kohla, Guido; Kannicht, Christoph; Wiedemann, Philipp; Hafner, Mathias; et al.
Abstract: N -glycosylated proteins produced in human embryonic kidney 293 (HEK 293) cells often carry terminal N -acetylgalactosamine (GalNAc) and only low levels of sialylation. On therapeutic proteins, such N -glycans often trigger rapid clearance from the patient's bloodstream via efficient binding to asialoglycoprotein receptor (ASGP-R) and mannose receptor (MR). This currently limits the use of HEK 293 cells for therapeutic protein production. To eliminate terminal GalNAc, we knocked-out GalNAc transferases B4GALNT3 and B4GALNT4 by CRISPR/Cas9 in FreeStyle 293-F cells. The resulting cell line produced a coagulation factor VII-albumin fusion protein without GalNAc but with increased sialylation. This glyco-engineered protein bound less efficiently to both the ASGP-R and MR in vitro and it showed improved recovery, terminal half-life and area under the curve in pharmacokinetic rat experiments. By overexpressing sialyltransferases ST6GAL1 and ST3GAL6 in B4GALNT3 and B4GALNT4 knock-out cells, we further increased factor VII-albumin sialylation; for ST6GAL1 even to the level of human plasma-derived factor VII. Simultaneous knock-out of B4GALNT3 and B4GALNT4 and overexpression of ST6GAL1 further lowered factor VII-albumin binding to ASGP-R and MR. This novel glyco-engineered cell line is well-suited for the production of factor VII-albumin and presumably other therapeutic proteins with fully human N -glycosylation and superior pharmacokinetic properties.